Pelaksanaan Kampanye Pemilihan Umum 2024 Menurut Undang-Undang Pemilihan Umum di Kota Tangerang - Fico Acchedya Wijaya; Rasji (Syntax Corporation, 2023)
In Indonesia, general election is considered as a democracy festive which periodically held once in 5 years. It is a moment once every five years, when all the participants of the election enliven the atmosphere of every city in the seek of every vote and support from the citizens, whose are in the capacity as voters in the upcoming general election. Things could be rough in every general election, this was caused by plenty of participants of the election, and also the president and the vice president candidates to choose from. This create a lot of different perspective and opinion, which sometimes caused a chaos. Plus, there is an absence of law in a form of penalty towards the regulation enforcement, which resulting upon this upcoming democracy festive to be in heated up. The research methodology used for this research is the normative methodology, this particular methodology is chosen in hope to find an answer upon the issues found, from the primary and secondary legal materials.